Sharia Financial Management Alternative Sources In Encouraging Micro, Small And Medium Enterprises Expansion In Indonesia - Suraiya, Nur (LPPM Universitas Terbuka, 2022)
Micro, Small, And Medium Enterprises (MSME) is one of the pillars of the Indonesian economy. Data in 2021 shows that the number of MSME in Indonesia has reached 64.2 million business units. However, it does not mean that MSME in Indonesia is far from all the problems. One of the problems experienced by MSME is that many business entrepreneurs do not understand how to manage the finances and assets they get. Hence, many MSME in Indonesia has gone bankruptcy. This study use qulitative methods. The data are obtained from existing scientific journals and provided by related parties as well as books that discuss financial management and MSME. The results obtained from this study are about how SME practices simple and easy to understand accounting activities and applies Islamic values. On the other hand, this study explains the way SME subjects invest with limited capital and also how to get capital that is far from riba (Interest).